Development of an automatic whiteboard eraser / Razif Omar - Omar, Razif (2004)
This project involved the development of conceptual ideas and initial designs layouts of a new Automatic Whiteboard Eraser mechanism. The mechanism is developed to be fast, easy to assemble and dissemble, can be install on any existing wall mounted whiteboard, manufacturable and low cost. Two programmes are developed using Microsoft Excel Spreadsheet to select and sizing the mechanism components. A working model of the developed mechanism was constructed to test its effectiveness.